BibTeX for the Romanian Language - MUREȘAN, Marian (Studia Universitatis Babeș-Bolyai Informatica, 2021)
BibTeX was created by Oren Patashnik and Leslie Lamport in 1985 according to https://en.wikipedia.org/wiki/BibTeX and turned out to be a very useful software product. Nevertheless most of the present scientific paper in mathematics and computer science, and not only, are written in English. Our aim was to offer to the Romanian scientific paper writers a variant of the BibTEX whose output agrees with the Romanian language grammar. Received by the editors: 2 May 2021. 2010 Mathematics Subject Classification. 97P40, 97R30. 1998 CR Categories and Descriptors. D.3.3 [Language Constructs and Features]: Modules, packages.